Transcriptomic and Metabolomic Exploration of the Therapeutic Effects of Prunus cerasifera Ehrh. Polyphenol on Metabolic-associated Fatty Liver Disease - Zaifu ZHOU; Yuxia WANG; Daohong CHEN; Hongbo REN; Quansong LIN (Shipin gongye ke-ji)
This study aimed to explore the therapeutic effect of Prunus cerasifera Ehrh. Polyphenol (PCP) on high-fat diet-induced metabolic associated fatty liver disease (MAFLD) and its mechanism. Fifty 6-week-old male C57BL/6 mice were randomly divided into a normal group, a model group, a low-dose PCP group (PCP-L, 250 mg/kg), and a high-dose PCP group (PCP-H, 500 mg/kg). A MAFLD model was established using a high-fat diet, and the intervention lasted for 12 weeks. The effects on mice's plasma biochemical indicators, liver tissue biochemical indicators, and liver tissue pathological morphology were observed. The effects of PCP on the liver transcriptome and serum bile acid metabolic profile of mice was also analyzed. The results showed that compared with the model (Mod) group, the levels of AST and ALT in the serum of PCP-L and PCP-H mice were significantly reduced (P<0.01 or P<0.05), and the levels of TC, TG, LDL-C, and FFA in the plasma were significantly decreased (P<0.01 or P<0.05), while the level of HDL-C was notably increased (P<0.01 or P<0.05). In liver tissue, PCP significantly reduced the content of TG and TC (P<0.01 or P<0.05), decreased the levels of pro-inflammatory factors IL-6, IL-1β, and TNF-α (P<0.01 or P<0.05), and increased the levels of liver SOD and GSH (P<0.01 or P<0.05), while reducing the level of MDA (P<0.01 or P<0.05). Histopathological examination of the liver showed that PCP could improve the pathological state of the liver. Transcriptomic results indicated that biological processes such as inflammatory response, lipid metabolism, oxidative stress response, and cell proliferation were significantly upregulated after PCP treatment, with key genes related to lipid metabolism and bile acid synthesis being notably upregulated. Bile acid metabolomic results showed significant changes in the concentration of bile acids such as hyodeoxycholic acid, ursodeoxycholic acid, taurochenodeoxycholic acid, glycocholic acid, and glycoursodeoxycholic acid after PCP treatment. In summary, PCP has a significant therapeutic effect on MAFLD through the regulation of the transcriptome and bile acid metabolism, providing a scientific basis for its potential as a natural product for the treatment of MAFLD.